An exploratory study on the introduction of multistream management to business and economics students of De La Salle University - Marasigan, Ma. C.P. Assumpta C. (Animo Repository, 2013)
This study explored what business and economics students taking up an introductory general management course thought of as effective management after having been exposed to two approaches. The mainstream or traditional approach emphasizes financial wellbeing for shareholders. The multistream approach considers other forms of wellbeing (e.g., emotional, social, and physical) for shareholders and other stakeholders. The study revealed that after having been exposed for eighteen 1½-hour class sessions to both approaches, on the average, the students did not seem to favor one approach over another. However, the responses of those students who had had religion classes in high school differed significantly from those of students who had not had religion classes in high school. The first group tended to favor the multistream approach over the mainstream approach. This finding could be the basis of the inclusion of lessons on cardinal virtues in a required religion class in college.